2023
DOI: 10.3390/agronomy13030716
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Properties Retrieval from Sentinel-2 Satellite Data and Machine Learning Algorithms

Abstract: The accurate monitoring of soil salinization plays a key role in the ecological security and sustainable agricultural development of semiarid regions. The objective of this study was to achieve the best estimation of electrical conductivity variables from salt-affected soils in a south Mediterranean region using Sentinel-2 multispectral imagery. In order to realize this goal, a test was carried out using electrical conductivity (EC) data collected in central Tunisia. Soil electrical conductivity and leaf elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 92 publications
1
1
0
Order By: Relevance
“…This shows that RF and DT are more powerful in modeling highly nonlinear dimensional relationships than XGBoost and SVR. Our findings concur with those found in 95 , 96 . Merembayev et al 97 indicated that DT and RF have almost the same performance for soil salinity estimation, which is aligned with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…This shows that RF and DT are more powerful in modeling highly nonlinear dimensional relationships than XGBoost and SVR. Our findings concur with those found in 95 , 96 . Merembayev et al 97 indicated that DT and RF have almost the same performance for soil salinity estimation, which is aligned with our findings.…”
Section: Discussionsupporting
confidence: 93%
“…It interferes with numerous physiological, biochemical, and molecular processes [ 1 ]. The use of low-quality water (brackish water, reclaimed water, drainage), often with high salinity levels, is becoming increasingly important in order to overcome water scarcity and to meet the growing demand for water for agricultural development [ 2 , 3 , 4 , 5 ]. Olives, one of the most important tree crops in the Mediterranean, are often exposed to high salinity levels in the root zone, especially during long, hot, and dry summers [ 2 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%